The welfare effects of inflation: a cost-benefit perspective - Karl-Heinz Tödter; Bernhard Manzke (Deutsche Bundesbank, 2007)
This paper reviews theory and evidence of the welfare effects of inflation from a costbenefit perspective. Basic models and selected empirical results are discussed. Historically, in assessing the welfare effects of inflation, the distortion of money demand played a prominent role. More recently, interactions of inflation and taxation came into focus. Growth effects of inflation as well as welfare effects of unanticipated inflation and of inflation uncertainty are also addressed. To assess the policy question whether inflation should be reduced or eliminated, the costs of disinflation play a role. Finally, the trade-off between the benefits of reducing inflation and the costs of disinflation is discussed and an overall assessment of the net welfare effects of achieving price stability is provided.
Keywords: E41; E31; H21; E21; D61; 330; Inflation; price stability; welfare costs and benefits; distortions; money demand; consumption allocation; tax-inflation interaction; Inflation; Wohlfahrtseffekt; Inflationsbekämpfung; Preisniveaustabilität; Kosten-Nutzen-Analyse; Theorie; Welt